Sensitivity Analysis and Multiobjective Optimization of CO2 Huff-N-Puff Process after Water Flooding in Natural Fractured Tight Oil Reservoirs - Zhang Jie; Cai Ming-Jun; Ge Dangke; Lu Ning; Cheng Hai-Ying; Wang Hai-Feng; Li Rong-Tao (Geofluids)
The CO2 huff-n-puff is an effective substitute technology to further improve oil recovery of natural fractured tight oil reservoirs after water flooding, for its high displacement efficiency and superior injectivity. The CO2 huff-n-puff process is influenced by many factors, such as miscible degree, complex fracture networks, and production schemes. What is worse, those influence facts affect each other making the process more complex. Many researchers concentrated on mechanisms and single sensitivity analysis of CO2 huff-n-puff process, whereas few optimized this process with the consideration of all influence factors and multiobjective to get favorable performance. We built multiobjective consisted of miscible degree, oil recovery, and gas replacing oil rate considering the aspects of CO2 flooding special characteristic, technical effectiveness, and economic feasibility, respectively. We have taken Yuan 284 tight oil block as a case, firstly investigated sensitivity analysis, and then optimized CO2 huff-n-puff process using orthogonal experiment design with multifactors and multiobjectives. The optimization results show CO2 huff-n-puff can significantly improve oil recovery by 8.87% original oil in place (OOIP) compared with water flooding, which offers guidelines for field operations.